2016
DOI: 10.3847/0004-637x/820/2/92
|View full text |Cite
|
Sign up to set email alerts
|

SN 2012cg: EVIDENCE FOR INTERACTION BETWEEN A NORMAL SN Ia AND A NON-DEGENERATE BINARY COMPANION

Abstract: We report evidence for excess blue light from the Type Ia supernova (Sn Ia) SN2012cg at 15 and 16 days before maximum B-band brightness. The emission is consistent with predictions for the impact of the supernova on a nondegenerate binary companion. This is the first evidence for emission from a companion to a normal SNIa. Sixteen days before maximum light, the B V -color of SN2012cg is 0.2 mag bluer than for other normal SNIa. At later times, this supernova has a typical SNIa light curve, with extinction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
203
1
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(214 citation statements)
references
References 91 publications
(152 reference statements)
8
203
1
2
Order By: Relevance
“…In addition, it was found that the light curve of SN 2012cg was slightly narrower than that of a typical normal SN Ia, namely SN 2011fe . They also estimated the explosion date of SN 2012cg to be May 15.7 (UT), which is consistent with the explosion time of MJD=56062.5 (May 15.5 UT) estimated by Marion et al (2016). The green triangles represent the sub-Ch-mass scenario.…”
Section: Sn 2012cgsupporting
confidence: 65%
See 4 more Smart Citations
“…In addition, it was found that the light curve of SN 2012cg was slightly narrower than that of a typical normal SN Ia, namely SN 2011fe . They also estimated the explosion date of SN 2012cg to be May 15.7 (UT), which is consistent with the explosion time of MJD=56062.5 (May 15.5 UT) estimated by Marion et al (2016). The green triangles represent the sub-Ch-mass scenario.…”
Section: Sn 2012cgsupporting
confidence: 65%
“…2 can only be shifted by about a factor of two due to the uncertainties of fitting parameters among different MS (or RG) companion stars. Marion et al (2016) presented early-time photometry of SN 2012cg, showing that blue excess light is seen at about 16 days before maximum B-band brightness. They reported that this blue early-time excess is consistent with predicted early-time emission of shocked gas that was proposed by Kasen (2010), suggesting SN 2012cg was generated from a binary system in the SD Ch-mass scenario.…”
Section: Searching For Stripped Hydrogenmentioning
confidence: 99%
See 3 more Smart Citations